2020
DOI: 10.5187/jast.2020.62.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different standardized ileal digestible lysine: net energy proportion in growing and finishing pigs

Abstract: This experiment was performed to evaluate the optimal proportion of dietary standardized ileal digestible lysine (SID Lys) to net energy (NE) proportion in growing to finishing pigs. A total of seventy-two pigs were used at phase 1 (initial body weight 37.23 ± 0.23 kilogram, for 42 d) and at phase 2 (initial body weight 54.16 ± 0.20 kilogram, for 77 d). They were arbitrarily assigned to three treatments groups consisting of four duplicates per treatment (six pigs in duplicates, respectively). Diet treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…These results match those observed in earlier studies which did not find differences in carcass traits using different phase feeding strategies [18,22,40]. Nevertheless, previous literature also found that lean meat % increases as space allowance decreases [1], and fat thickness increases as SID Lys:NE ratio decreases [48,49,51]. Although these findings were not observed in the present study, an interaction tendency was observed between space allowance and phase feeding on lean meat % and fat thickness in trial 1, and these two traits were numerically different in trial 2 when reducing the SID lys:NE ratio from 0.95 to 0.82.…”
Section: Carcass Traitssupporting
confidence: 91%
See 1 more Smart Citation
“…These results match those observed in earlier studies which did not find differences in carcass traits using different phase feeding strategies [18,22,40]. Nevertheless, previous literature also found that lean meat % increases as space allowance decreases [1], and fat thickness increases as SID Lys:NE ratio decreases [48,49,51]. Although these findings were not observed in the present study, an interaction tendency was observed between space allowance and phase feeding on lean meat % and fat thickness in trial 1, and these two traits were numerically different in trial 2 when reducing the SID lys:NE ratio from 0.95 to 0.82.…”
Section: Carcass Traitssupporting
confidence: 91%
“…Therefore, the relationship between space allowance, phase feeding and productive performance may vary between batches, due to interactions of different environmental/management factors such as mixing and should be checked for repeatability in further studies. Finally, it is worth mentioning that the high levels of SID Lys:NE ratio used at the late finishing stage may increase the levels of NH 3 [47,49,50] which is contrary to farm sustainability because it contributes to the environment pollution [21].…”
Section: Space Allowance × Mixing (Trials 1 and 2)mentioning
confidence: 99%
“…Noteworthy, increasing the protein diet to such levels may increase the levels of NH 3 and affect the environment and farm sustainability (Lee et al, 2020; Liu et al, 2015). Then, to reach the described levels of SID Lys/AA may not be feasible, although the environmental impact could be minimized by formulating diets using synthetic amino acids which allows to reduce the crude protein levels while maintaining the nutrient requirements, performance and carcass quality (Prandini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…over the past few years [13,14]. The mechanism for the potential additional benefit of feeding above generally accepted net energy and lysine requirements in improving pig growth performance may involve enhanced nutrient utilization and metabolic efficiency, possibly through the stimulation of protein synthesis [15]. However, employing a low-lysine diet was not effective in enhancing the intramuscular fat content or improving the eating quality of pork muscle in finishing pigs with high slaughter weights [16].…”
Section: Introductionmentioning
confidence: 99%